Implementación de un manual de buenas prácticas de manufactura en el proceso de elaboración del chocolate en la empresa kaacao S.A. - Mendoza Marcillo, Ángela María (2024)
The objective of this research was to implement a GMP manual that contributes to the safety of chocolate production in the company Kaacao S.A. A compliance checklist was made according to ARCSA 067, where the following were evaluated: facilities, personnel obligations, production operations, packaging, labeling and packing, storage, distribution, transportation and marketing, quality assurance and control, whose initial diagnosis showed 85% compliance and 15% non-compliance in the quality assurance and control criteria. Microbiological analysis was performed on the chocolate bars, the results showed the presence of mesophilic aerobes (9.0 x105 CFU/g), total coliforms (8.3 x102 CFU/g) and yeasts (4, 9 x103 CFU/g) in 65% cocoa chocolate and mesophilic aerobes (8.2 x105 CFU/g), total coliforms (3.0 x102 CFU/g), absence of yeasts in 75% chocolate; both samples were free of molds and salmonella according to INEN 621. The GMP manual was designed and implemented and 96% compliance with ARCSA 067 criteria was verified, while microbiological results showed 2.0x104 CFU/g of mesophilic aerobes, absence of total coliforms and salmonella, 1.0x102 CFU/g for molds in both samples and yeasts of 4.0x102 CFU/g (65% cocoa) and 1.0x102 CFU/g (75% cocoa), obtaining an improvement >80%, being for the 75% bar an improvement >60 in mesophilic aerobes. Therefore, the implementation of GMPs was able to improve the microbiological quality of the chocolate bars of Kaacao S.A. company.